Analysis of Corporate Zakat on the Capital Structure of Islamic Banks in Indonesia - Nanda Lismatiara Zubaid; Risma Savhira Dwi Lestari; Tika Widiastuti; Mochammad Soleh; Anwar M. Radiamoda (AFEBI Islamic Finance and Economic Review, 2022)
Zakat has similarities with taxes but also differs in several respects. Zakat is an Islamic commandment, while taxes are a government order; and zakat aims to meet the needs of the poor, while taxes aim to meet the expenditure of society as a whole. Companies that only pay taxes and companies that pay taxes and zakat have many differences such as in profitability and capital structure. Most Muslims are busy with tax matters for fear of being punished for the crime of tax evasion. But they forget Allah's right in wealth and anyone who refuses to fulfill it is unlawful. Contemporary application of zakat should be a concern of the people.